Comparative iTRAQ-based quantitative proteomic analysis of spotted seal (Phoca largha) pups inhabiting different environments. Issue 1 (31st December 2022) - Tian, Jiashen; Wang, Zhen; Li, Xiang; Li, Xin; Kong, Zhongren; Zhang, Shengjiu; Li, Yingdong; Lu, Zhichuang
Abstract : Captive breeding is among the most effective approaches for ensuring the conservation of numerous endangered species. However, only a few studies have examined the effects of captive maintenance of animals at the molecular level. In this study, we adopted the isobaric tags for relative and absolute quantification (iTRAQ) approach to compare protein expression in the blood of endangered spotted seal pups ( Phoca largha ) inhabiting different environments. We identified 519 proteins from 2, 628 peptides, the expression of 158 of which differed significantly between short-term captive and wild seals. In addition, 140 proteins were identified as being differentially expressed between short-term and long-term captive seals, whereas 235 proteins were differentially expressed between the wild and long-term captive groups ( p < 0.05). In wild seal pups, proteins associated with the maintenance of cardiomyocyte cell stability and integrity, protection of the heart, and prevention of anemia were upregulated, reflecting the high stress and energetic costs associated with movement and foraging. In addition, significant differences were detected among the three groups with respect to immune-related proteins. The results of this study advance our current understanding of protein expression in spotted seals and provide data that will contribute to the future conservation of this species.